DEVELOPMENT OF THE UNIVERSITY ELECTRONIC INFORMATION ENVIRONMENT - Natalya G. Zakrevskaya; Sergey S. Filippov (Moscow Polytechnic University, 2016)
The article highlights the features of the University Electronic Information Environment, its organizational structure and its components, the law papers of all levels essential for its functioning and development. The main components of the Electronic Information Environment are electronic information resources, apparatus equipment, organizational component, action schedule (local acts), and educational technologies. The authors dwell on the role of the University Library in the University Electronic Information Environment. Today it is the centre of global informatization of educational and research processes.